Biotechnological application of Streptomyces for the production of clinical drugs and other bioactive molecules. (October 2022) - Del Carratore, Francesco; Hanko, Erik KR; Breitling, Rainer; Takano, Eriko
Abstract : Streptomyces is one of the most relevant genera in biotechnology, and its rich secondary metabolism is responsible for the biosynthesis of a plethora of bioactive compounds, including several clinically relevant drugs. The use of Streptomyces species for the manufacture of natural products has been established for more than half a century; however, the tremendous advances observed in recent years in genetic engineering and molecular biology have revolutionised the optimisation of Streptomyces as cell factories and drastically expanded the biotechnological potential of these bacteria. Here, we illustrate the most exciting advances reported in the past few years, with a particular focus on the approaches significantly improving the biotechnological capacity of Streptomyces to produce clinical drugs and other valuable secondary metabolites. Graphical Abstract: ga1 Highlights: A rational optimization of Streptomyces strains is possible. This can be achieved through rewiring of primary metabolism and regulatory networks. Biosynthetic gene cluster refactoring can improve production titres. Data-driven optimisation of fermentation conditions can help further optimisation. Streptomyces are a rich source of biocatalysts for biotransformation systems.